1976
DOI: 10.1111/j.1476-5381.1976.tb08626.x
|View full text |Cite
|
Sign up to set email alerts
|

The Local Antinociceptive and Topical Anti‐inflammatory Effects of Propyl Gallate in Rodents

Abstract: In common with several anti‐inflammatory, analgesic, local anaesthetic and antioxidant drugs, propyl gallate in vitro inhibited the biosynthesis of prostaglandin E2 and F2α from arachidonic acid by a prostaglandin synthetase from bull seminal vesicles. In common with analgesic drugs, propyl gallate reduced the ability of arachidonic acid, acetylcholine or acetic acid to cause abdominal constrictions in mice. Using a new method of evaluating anti‐inflammatory activity, we demonstrated the effectiveness of aspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Nugterin et al (1966) were first to demonstrate that high concentrations of Propyl Gallate inhibited prostaglandin synthesis in sheep seminal vesicles. McDonald-Gibson et al (1976) confirmed these findings (50% inhibitory concentration of 103 μM) using bull seminal vesicles in vitro. Panganamala et al (1977) reported that Propyl Gallate, at concentrations of 4 × 10 −4 M, inhibited the formation of prostaglandin from eicosa-8,11,14-trienoic acid by bovine seminal vesicle microsomes.…”
Section: Effects On Prostaglandins/anti-inflammatory Effectssupporting
confidence: 75%
See 1 more Smart Citation
“…Nugterin et al (1966) were first to demonstrate that high concentrations of Propyl Gallate inhibited prostaglandin synthesis in sheep seminal vesicles. McDonald-Gibson et al (1976) confirmed these findings (50% inhibitory concentration of 103 μM) using bull seminal vesicles in vitro. Panganamala et al (1977) reported that Propyl Gallate, at concentrations of 4 × 10 −4 M, inhibited the formation of prostaglandin from eicosa-8,11,14-trienoic acid by bovine seminal vesicle microsomes.…”
Section: Effects On Prostaglandins/anti-inflammatory Effectssupporting
confidence: 75%
“…The activity of Propyl Gallate in infiltration anesthesia was potentiated by epinephrine (Modak and Rao 1971). McDonald-Gibson et al (1976) studied the effect of Propyl Gallate on arachidonic acid (AA)-induced abdominal contractions in mice. Treatment consisted of intraperitoneal injection, subcutaneous injection, or oral ingestion of an AA-Propyl Gallate mixture, Propyl Gallate then AA, AA then Propyl Gallate, or AA and Propyl Gallate simultaneously.…”
Section: Neurological/neuromuscular Effectsmentioning
confidence: 99%
“…Recently, the antiinflammatory activity of n-propyl gallate was assessed in experimental animal models (Jung et al, 2010). It was also reported that n-propyl gallate contained topical antiinflammatory activity in a mouse ear edema test (McDonald-Gibson et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to estradiol, n-propyl gallate appeared to be relatively more estrogenic in the estrogen receptor-β cells than in the estrogen receptor-α cells [9]. Although anti-inflammatory activity of n-propyl gallate was preliminarily proposed [10], it has not been documented in detail. In this work, it is further demonstrated that n-propyl gallate shows antiinflammatory activity via down-regulation of nitric oxide (NO) and ROS levels.…”
mentioning
confidence: 99%